2020
DOI: 10.34257/gjmbrbvol20is4pg1
|View full text |Cite
|
Sign up to set email alerts
|

Driving Competitive Advantage: The Role of Strategic Entrepreneurship in Textile Manufacturing Firms in Lagos State, Nigeria

Abstract: The paper argued that the challenges experienced in Nigerian textile manufacturing firms resulted from weak strategic entrepreneurship leading to alarming decline in the industry’s performance. Thus, investigated competitive advantage nexus with strategic entrepreneurship (strategic flexibility, adaptability, innovation, strategic leadership, risk taking and dynamic capabilities) as proxies in Lagos State, Nigeria. A cross-sectional survey research design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The result of hypothesis one (H1) differs from that of Chebo and Wubatie (2020) [17] , Egwakhe et al (2020) [18] and Sajjad et al (2020) [64] . For example, Chebo & Wubatie (2020) [17] found that strategic flexibility has negative significant effect on competitive advantage in Ethiopia.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The result of hypothesis one (H1) differs from that of Chebo and Wubatie (2020) [17] , Egwakhe et al (2020) [18] and Sajjad et al (2020) [64] . For example, Chebo & Wubatie (2020) [17] found that strategic flexibility has negative significant effect on competitive advantage in Ethiopia.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, Chebo & Wubatie (2020) [17] found that strategic flexibility has negative significant effect on competitive advantage in Ethiopia. In addition, while Sajjad et al (2020) [64] established that strategic flexibility has no effect on performance of SMEs in sport goods manufacturing sector in Pakistan, Egwakhe et al (2020) [18] found that strategic flexibility has no significant relationship with competitive advantage of sampled textile manufacturing firms in Lagos State, Nigeria. It becomes imperative from the findings of the study that firms in dynamic business environment can improve and sustain performance by creating multiple strategic options their resources can be applied and coordinated to meet changing consumer needs, as well as proactively preparing and reacting effectively to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the small population size, the need for sampling becomes unnecessary. Total enumeration was applied as evident in previous scholars works (Makinde and Agu 2018;Tijani and Akinlabi, 2020;Nwangwu, Ozigbo, Ngige, and Ugwu, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The foundation of the survival strategy is that to survive, SME firms need to constantly adapt to their competitive financial climate. Brian (1996) cited in Egwakhe et al, (2020) opined that a new way of thinking about the business world (a paradigm) and new ways of behaving (corporate strategies) seem to be introduced every decade.…”
Section: Survival-based Theorymentioning
confidence: 99%
“…This theory, which was very popular during the late 19th and early 20th centuries, stressed the notion that only the best and fittest of MSME competitors would benefit by pursuing the concept of design, which eventually would lead to the development of a creative and innovative service or product. The survival-based view of the management emphasized the assumption that businesses that follow financial strategies that focus on running very productive activities would thrive in a competitive environment (Egwakhe, et al, 2020;Octasylva, et al, 2022). These scholars concluded that the most equipped and willing MSME owners and start-up entrepreneurs that adapt to the favourable financial and environmental business climate is the organisation that succeeds.…”
Section: Survival-based Theorymentioning
confidence: 99%